2008
DOI: 10.1136/vr.162.14.436
|View full text |Cite
|
Sign up to set email alerts
|

Dog‐human and dog‐dog interactions of 260 dog‐owning households in a community in Cheshire

Abstract: This study investigated the nature and frequency of the contacts that occur between dogs, and between dogs and people, by means of a questionnaire survey of 260 dog-owning households in a community in Cheshire, uk. The contacts were highly variable and were affected by the size, sex and age of the dog, individual dog behaviours, human behaviours and human preferences in the management of the dog. A number of situations were identified that may be important in relation to zoonoses, including sleeping areas, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 28 publications
12
122
3
1
Order By: Relevance
“…Similar results were reported for jumping on people in Cheshire, United Kingdom (Westgarth et al, 2008), and for aggressive behaviors in Mexico (Edwards et al, 2002) and in a referral practice in Spain (Fatjo et al, 2007). On the other hand, previous findings in Iran regarding the rate of aggressive behaviors toward other dogs (21%) (Khoshnegah et al, 2011) were significantly different from what was reported in our survey (50.4%).…”
Section: Discussionsupporting
confidence: 49%
“…Similar results were reported for jumping on people in Cheshire, United Kingdom (Westgarth et al, 2008), and for aggressive behaviors in Mexico (Edwards et al, 2002) and in a referral practice in Spain (Fatjo et al, 2007). On the other hand, previous findings in Iran regarding the rate of aggressive behaviors toward other dogs (21%) (Khoshnegah et al, 2011) were significantly different from what was reported in our survey (50.4%).…”
Section: Discussionsupporting
confidence: 49%
“…However, in other studies, including our previous work with United Kingdom vet-visiting dogs and healthy pet dogs in the community, the prevalence of C. jejuni appears to be relatively low (30,33,34,43,45). In such populations, it is therefore likely that the overall zoonotic risk is low, although where an individual dog does carry C. jejuni, the risk may be high, depending on factors such as the level of contact between the dogs and humans (42). Such instances may account for case reports of dog-human transmission (8,47).…”
Section: Discussionmentioning
confidence: 84%
“…However, the VOL. 47,2009 TYPING OF CANINE C. JEJUNI ISOLATES BY MLST AND PFGE 3469 exposure risk to dogs and thus possibly humans for certain sequence types may differ depending upon the circumstances of the dog (42).…”
Section: Discussionmentioning
confidence: 99%
“…Within the social sciences, investigations into the relationships between spatial and temporal patterns of dog-walking, dog-to-dog contact, and dog demographics have indirectly explored behaviours that could influence the risk of GI disease transmission in dogs [3,[11][12][13]. However, only a limited number of studies have investigated the extent to which parks might pose risks for infection and transmission of GI parasites in dogs [2,7,9,[13][14][15][16][17][18][19][20][21], a relevant query given that in urban settings, parks figure prominently as dog-walking destinations [22].…”
Section: Introductionmentioning
confidence: 99%